Rhizosphere microbiome selection by Epichloë endophytes of Festuca arundinacea - Roberts, Elizabeth Lewis; Ferraro, Aileen (Plant and Soil, 2015)
Aims: Loline alkaloids produced by Epichloë spp. are known to deter feeding by insect herbivores while also serving as a significant carbon source for certain epiphytic bacteria on tall fescue leaves. In this study we examined the role of loline alkaloids in attracting certain bacteria to the rhizosphere of tall fescue plants that harbor loline producing fungal endophytes. Methods: Population studies were used to compare the fitness of known loline catabolizing strains to other rhizosphere bacteria. Pyrosequencing of 16S rRNA fragments compared the composition of bacterial communities inhabiting the endophyte infected tall fescue (Festuca arundinacea) rhizosphere to those of endophyte free fescue plants. Results: Rhizosphere population studies demonstrated that loline catabolizing strains Burkholderia ambifaria 7R and Pseudomonas aureofaciens outcompete and suppress the growth of non-loline catabolizing strains. Pyrosequencing of 16S rRNA fragments showed greater percentages of certain plant growth promoting bacteria in rhizosperes seeded with B. ambifaria 7R than non-inoculated soils. Rhizospheres of endophyte infected plants showed higher species richness (Shannon diversity index = 4.03) over endophyte free rhizospheres (Shannon diversity index = 3.08) and a greater percentage of Firmicutes. Conclusions: The differences in microbial community composition between endophyte-infected and endophyte-free rhizospheres suggest that the presence of fungal endophytes influences microbial community structure. Loline alkaloid production may be one proxy by which the fungal endophyte shapes microbial communities, as evidenced by increased fitness of loline catabolizing bacteria in the tall fescue rhizosphere. © 2015, Springer International Publishing Switzerland.
21 citations (Crossref) [2023-10-31] Citation Key Alias: pop00270 tex.type: [object Object]
Keywords: Bacteria (microorganisms); Burkholderia ambifaria; Endophyte; Epichloë spp; Festuca arundinacea; Firmicutes; Hexapoda; Loline alkaloids; Pseudomonas chlororaphis; Tall fescue; alkaloid; antifeedant; bacterium; community structure; dept.bio; diversity index; endophyte; fitness; fungus; grass; insect; microbial community; microorganism; rhizosphere; species richness

Designing a broad-spectrum integrative approach for cancer prevention and treatment. - Block, Keith I; Gyllenhaal, Charlotte; Lowe, Leroy; Amedei, Amedeo; Amin, A R M Ruhul; Amin, Amr; Aquilano, Katia; Arbiser, Jack; Arreola, Alexandra; Arzumanyan, Alla; Ashraf, S Salman; Azmi, Asfar S; et al. (Seminars in Cancer Biology, 2015)
Targeted therapies and the consequent adoption of "personalized" oncology have achieved notable successes in some cancers; however, significant problems remain with this approach. Many targeted therapies are highly toxic, costs are extremely high, and most patients experience relapse after a few disease-free months. Relapses arise from genetic heterogeneity in tumors, which harbor therapy-resistant immortalized cells that have adopted alternate and compensatory pathways (i.e., pathways that are not reliant upon the same mechanisms as those which have been targeted). To address these limitations, an international task force of 180 scientists was assembled to explore the concept of a low-toxicity "broad-spectrum" therapeutic approach that could simultaneously target many key pathways and mechanisms. Using cancer hallmark phenotypes and the tumor microenvironment to account for the various aspects of relevant cancer biology, interdisciplinary teams reviewed each hallmark area and nominated a wide range of high-priority targets (74 in total) that could be modified to improve patient outcomes. For these targets, corresponding low-toxicity therapeutic approaches were then suggested, many of which were phytochemicals. Proposed actions on each target and all of the approaches were further reviewed for known effects on other hallmark areas and the tumor microenvironment. Potential contrary or procarcinogenic effects were found for 3.9% of the relationships between targets and hallmarks, and mixed evidence of complementary and contrary relationships was found for 7.1%. Approximately 67% of the relationships revealed potentially complementary effects, and the remainder had no known relationship. Among the approaches, 1.1% had contrary, 2.8% had mixed and 62.1% had complementary relationships. These results suggest that a broad-spectrum approach should be feasible from a safety standpoint. This novel approach has potential to be relatively inexpensive, it should help us address stages and types of cancer that lack conventional treatment, and it may reduce relapse risks. A proposed agenda for future research is offered. Copyright © 2015 The Authors. Published by Elsevier Ltd.. All rights reserved.
196 citations (Crossref) [2023-10-31] Place: England Block, Keith I. Block Center for Integrative Cancer Treatment, Skokie, IL, United States. Electronic address: drblock@blockmedical.com. Gyllenhaal, Charlotte. Block Center for Integrative Cancer Treatment, Skokie, IL, United States. Lowe, Leroy. Getting to Know Cancer, Truro, Nova Scotia, Canada; Lancaster Environment Centre, Lancaster University, Bailrigg, Lancaster, United Kingdom. Electronic address: Leroy.lowe@gettingtoknowcancer.org. Amedei, Amedeo. Department of Experimental and Clinical Medicine, University of Florence, Florence, Italy. Amin, A R M Ruhul. Winship Cancer Institute of Emory University, Atlanta, GA, United States. Amin, Amr. Department of Biology, College of Science, United Arab Emirates University, Al Ain, United Arab Emirates. Aquilano, Katia. Department of Biology, University of Rome "Tor Vergata", Rome, Italy. Arbiser, Jack. Winship Cancer Institute of Emory University, Atlanta, GA, United States; Atlanta Veterans Administration Medical Center, Atlanta, GA, United States; Department of Dermatology, Emory University School of Medicine, Emory University, Atlanta, GA, United States. Arreola, Alexandra. Lineberger Comprehensive Cancer Center, University of North Carolina, Chapel Hill, NC, United States. Arzumanyan, Alla. Department of Biology, Temple University, Philadelphia, PA, United States. Ashraf, S Salman. Department of Chemistry, College of Science, United Arab Emirates University, Al Ain, United Arab Emirates. Azmi, Asfar S. Department of Oncology, Karmanos Cancer Institute, Wayne State University, Detroit, MI, United States. Benencia, Fabian. Department of Biomedical Sciences, Ohio University, Athens, OH, United States. Bhakta, Dipita. School of Chemical and Bio Technology, SASTRA University, Thanjavur, Tamil Nadu, India. Bilsland, Alan. University of Glasgow, Glasgow, United Kingdom. Bishayee, Anupam. Department of Pharmaceutical Sciences, College of Pharmacy, Larkin Health Sciences Institute, Miami, FL, United States. Blain, Stacy W. Department of Pediatrics, State University of New York, Downstate Medical Center, Brooklyn, NY, United States. Block, Penny B. Block Center for Integrative Cancer Treatment, Skokie, IL, United States. Boosani, Chandra S. Department of BioMedical Sciences, School of Medicine, Creighton University, Omaha, NE, United States. Carey, Thomas E. Head and Neck Cancer Biology Laboratory, University of Michigan, Ann Arbor, MI, United States. Carnero, Amancio. Instituto de Biomedicina de Sevilla, Consejo Superior de Investigaciones Cientificas, Seville, Spain. Carotenuto, Marianeve. Centro di Ingegneria Genetica e Biotecnologia Avanzate, Naples, Italy; Department of Molecular Medicine and Medical Biotechnology, Federico II, Via Pansini 5, 80131 Naples, Italy. Casey, Stephanie C. Stanford University, Division of Oncology, Department of Medicine and Pathology, Stanford, CA, United States. Chakrabarti, Mrinmay. Department of Pathology, Microbiology, and Immunology, University of South Carolina, School of Medicine, Columbia, SC, United States. Chaturvedi, Rupesh. School of Biotechnology, Jawaharlal Nehru University, New Delhi, India. Chen, Georgia Zhuo. Winship Cancer Institute of Emory University, Atlanta, GA, United States. Chen, Helen. Department of Pediatrics, University of British Columbia, Michael Cuccione Childhood Cancer Research Program, Child and Family Research Institute, Vancouver, British Columbia, Canada. Chen, Sophie. Ovarian and Prostate Cancer Research Laboratory, Guildford, Surrey, United Kingdom. Chen, Yi Charlie. Department of Biology, Alderson Broaddus University, Philippi, WV, United States. Choi, Beom K. Cancer Immunology Branch, Division of Cancer Biology, National Cancer Center, Goyang, Gyeonggi, Republic of Korea. Ciriolo, Maria Rosa. Department of Biology, University of Rome "Tor Vergata", Rome, Italy. Coley, Helen M. Faculty of Health and Medical Sciences, University of Surrey, Guildford, Surrey, United Kingdom. Collins, Andrew R. Department of Nutrition, Faculty of Medicine, University of Oslo, Oslo, Norway. Connell, Marisa. Department of Pediatrics, University of British Columbia, Michael Cuccione Childhood Cancer Research Program, Child and Family Research Institute, Vancouver, British Columbia, Canada. Crawford, Sarah. Cancer Biology Research Laboratory, Southern Connecticut State University, New Haven, CT, United States. Curran, Colleen S. School of Medicine and Public Health, University of Wisconsin-Madison, Madison, WI, United States. Dabrosin, Charlotta. Department of Oncology and Department of Clinical and Experimental Medicine, Linkoping University, Linkoping, Sweden. Damia, Giovanna. Department of Oncology, Istituto Di Ricovero e Cura a Carattere Scientifico - Istituto di Ricerche Farmacologiche Mario Negri, Milan, Italy. Dasgupta, Santanu. Department of Cellular and Molecular Biology, the University of Texas Health Science Center at Tyler, Tyler, TX, United States. DeBerardinis, Ralph J. Children's Medical Center Research Institute, University of Texas - Southwestern Medical Center, Dallas, TX, United States. Decker, William K. Department of Pathology & Immunology, Baylor College of Medicine, Houston, TX, United States. Dhawan, Punita. Department of Surgery and Cancer Biology, Division of Surgical Oncology, Vanderbilt University School of Medicine, Nashville, TN, United States. Diehl, Anna Mae E. Department of Medicine, Duke University Medical Center, Durham, NC, United States. Dong, Jin-Tang. Winship Cancer Institute of Emory University, Atlanta, GA, United States. Dou, Q Ping. Department of Oncology, Karmanos Cancer Institute, Wayne State University, Detroit, MI, United States. Drew, Janice E. Rowett Institute of Nutrition and Health, University of Aberdeen, Aberdeen, Scotland, United Kingdom. Elkord, Eyad. College of Medicine & Health Sciences, United Arab Emirates University, Al Ain, United Arab Emirates. El-Rayes, Bassel. Department of Hematology and Medical Oncology, Emory University, Atlanta, GA, United States. Feitelson, Mark A. Department of Biology, Temple University, Philadelphia, PA, United States. Felsher, Dean W. Stanford University, Division of Oncology, Department of Medicine and Pathology, Stanford, CA, United States. Ferguson, Lynnette R. Discipline of Nutrition and Auckland Cancer Society Research Centre, University of Auckland, Auckland, New Zealand. Fimognari, Carmela. Dipartimento di Scienze per la Qualita della Vita Alma Mater Studiorum-Universita di Bologna, Rimini, Italy. Firestone, Gary L. Department of Molecular & Cell Biology, University of California Berkeley, Berkeley, CA, United States. Frezza, Christian. Medical Research Council Cancer Unit, University of Cambridge, Hutchison/MRC Research Centre, Cambridge, United Kingdom. Fujii, Hiromasa. Department of Orthopedic Surgery, Nara Medical University, Kashihara, Nara, Japan. Fuster, Mark M. Medicine and Research Services, Veterans Affairs San Diego Healthcare System & University of California, San Diego, CA, United States. Generali, Daniele. Department of Medical, Surgery and Health Sciences, University of Trieste, Trieste, Italy; Molecular Therapy and Pharmacogenomics Unit, Azienda Ospedaliera Istituti Ospitalieri di Cremona, Cremona, Italy. Georgakilas, Alexandros G. Physics Department, School of Applied Mathematics and Physical Sciences, National Technical University of Athens, Athens, Greece. Gieseler, Frank. First Department of Medicine, University Hospital Schleswig-Holstein, Campus Lubeck, Lubeck, Germany. Gilbertson, Michael. Getting to Know Cancer, Guelph, Canada. Green, Michelle F. Duke Molecular Physiology Institute, Duke University Medical Center, Durham, NC, United States. Grue, Brendan. Departments of Environmental Science, Microbiology and Immunology, Dalhousie University, Halifax, Nova Scotia, Canada. Guha, Gunjan. School of Chemical and Bio Technology, SASTRA University, Thanjavur, Tamil Nadu, India. Halicka, Dorota. Department of Pathology, New York Medical College, Valhalla, NY, United States. Helferich, William G. University of Illinois at Urbana Champaign, Champaign, IL, United States. Heneberg, Petr. Charles University in Prague, Third Faculty of Medicine, Prague, Czech Republic. Hentosh, Patricia. School of Medical Laboratory and Radiation Sciences, Old Dominion University, Norfolk, VA, United States. Hirschey, Matthew D. Department of Medicine, Duke University Medical Center, Durham, NC, United States; Duke Molecular Physiology Institute, Duke University Medical Center, Durham, NC, United States. Hofseth, Lorne J. College of Pharmacy, University of South Carolina, Columbia, SC, United States. Holcombe, Randall F. Tisch Cancer Institute, Mount Sinai School of Medicine, New York, NY, United States. Honoki, Kanya. Department of Orthopedic Surgery, Nara Medical University, Kashihara, Nara, Japan. Hsu, Hsue-Yin. Department of Life Sciences, Tzu-Chi University, Hualien, Taiwan. Huang, Gloria S. Albert Einstein College of Medicine and Montefiore Medical Center, Bronx, NY, United States. Jensen, Lasse D. Department of Medical and Health Sciences, Linkoping University, Linkoping, Sweden; Department of Microbiology, Tumor and Cell Biology, Karolinska Institutet, Stockholm, Sweden. Jiang, Wen G. Cardiff University School of Medicine, Heath Park, Cardiff, United Kingdom. Jones, Lee W. Department of Medicine, Memorial Sloan-Kettering Cancer Center, New York, NY, United States. Karpowicz, Phillip A. University of Windsor, Windsor, Ontario, Canada. Keith, W Nicol. University of Glasgow, Glasgow, United Kingdom. Kerkar, Sid P. Laboratory Medicine and Pathology, Mayo Clinic, Rochester, MN, United States. Khan, Gazala N. Henry Ford Hospital, Detroit, MI, United States. Khatami, Mahin. Inflammation and Cancer Research, National Cancer Institute (Retired), National Institutes of Health, Bethesda, MD, United States. Ko, Young H. University of Maryland BioPark, Innovation Center, KoDiscovery, Baltimore, MD, United States. Kucuk, Omer. Winship Cancer Institute of Emory University, Atlanta, GA, United States. Kulathinal, Rob J. Department of Biology, Temple University, Philadelphia, PA, United States. Kumar, Nagi B. Moffitt Cancer Center, University of South Florida College of Medicine, Tampa, FL, United States. Kwon, Byoung S. Cancer Immunology Branch, Division of Cancer Biology, National Cancer Center, Goyang, Gyeonggi, Republic of Korea; Department of Medicine, Tulane University Health Sciences Center, New Orleans, LA, United States. Le, Anne. The Sol Goldman Pancreatic Cancer Research Center, Department of Pathology, Johns Hopkins University School of Medicine, Baltimore, MD, United States. Lea, Michael A. New Jersey Medical School, Rutgers University, Newark, NJ, United States. Lee, Ho-Young. College of Pharmacy, Seoul National University, South Korea. Lichtor, Terry. Department of Neurosurgery, Rush University Medical Center, Chicago, IL, United States. Lin, Liang-Tzung. Department of Microbiology and Immunology, School of Medicine, College of Medicine, Taipei Medical University, Taipei, Taiwan. Locasale, Jason W. Division of Nutritional Sciences, Cornell University, Ithaca, NY, United States. Lokeshwar, Bal L. Department of Medicine, Georgia Regents University Cancer Center, Augusta, GA, United States. Longo, Valter D. Andrus Gerontology Center, Division of Biogerontology, University of Southern California, Los Angeles, CA, United States. Lyssiotis, Costas A. Department of Molecular and Integrative Physiology and Department of Internal Medicine, Division of Gastroenterology, University of Michigan, Ann Arbor, MI, United States. MacKenzie, Karen L. Children's Cancer Institute Australia, Kensington, New South Wales, Australia. Malhotra, Meenakshi. Department of Biomedical Engineering, McGill University, Montreal, Canada. Marino, Maria. Department of Science, University Roma Tre, Rome, Italy. Martinez-Chantar, Maria L. Metabolomic Unit, Centro de Investigacion Biomedica en Red de Enfermedades Hepaticas y Digestivas, Technology Park of Bizkaia, Bizkaia, Spain. Matheu, Ander. Biodonostia Institute, Gipuzkoa, Spain. Maxwell, Christopher. Department of Pediatrics, University of British Columbia, Michael Cuccione Childhood Cancer Research Program, Child and Family Research Institute, Vancouver, British Columbia, Canada. McDonnell, Eoin. Duke Molecular Physiology Institute, Duke University Medical Center, Durham, NC, United States. Meeker, Alan K. Department of Pathology, Johns Hopkins University School of Medicine, Baltimore, MD, United States. Mehrmohamadi, Mahya. Field of Genetics, Genomics, and Development, Department of Molecular Biology and Genetics, Cornell University, Ithaca, NY, United States. Mehta, Kapil. Department of Experimental Therapeutics, University of Texas MD Anderson Cancer Center, Houston, TX, United States. Michelotti, Gregory A. Department of Medicine, Duke University Medical Center, Durham, NC, United States. Mohammad, Ramzi M. Department of Oncology, Karmanos Cancer Institute, Wayne State University, Detroit, MI, United States. Mohammed, Sulma I. Department of Comparative Pathobiology, Purdue University Center for Cancer Research, West Lafayette, IN, United States. Morre, D James. Mor-NuCo, Inc, Purdue Research Park, West Lafayette, IN, United States. Muralidhar, Vinayak. Harvard-MIT Division of Health Sciences and Technology, Harvard Medical School, Boston, MA, United States; Koch Institute for Integrative Cancer Research, Massachusetts Institute of Technology, Cambridge, MA, United States. Muqbil, Irfana. Department of Oncology, Karmanos Cancer Institute, Wayne State University, Detroit, MI, United States. Murphy, Michael P. MRC Mitochondrial Biology Unit, Wellcome Trust-MRC Building, Hills Road, Cambridge, United Kingdom. Nagaraju, Ganji Purnachandra. Department of Hematology and Medical Oncology, Emory University, Atlanta, GA, United States. Nahta, Rita. Winship Cancer Institute of Emory University, Atlanta, GA, United States. Niccolai, Elena. University of Florence, Florence, Italy. Nowsheen, Somaira. Medical Scientist Training Program, Mayo Graduate School, Mayo Medical School, Mayo Clinic, Rochester, MN, United States. Panis, Carolina. Laboratory of Inflammatory Mediators, State University of West Parana, UNIOESTE, Parana, Brazil. Pantano, Francesco. Medical Oncology Department, University Campus Bio-Medico, Rome, Italy. Parslow, Virginia R. Discipline of Nutrition and Auckland Cancer Society Research Centre, University of Auckland, Auckland, New Zealand. Pawelec, Graham. Center for Medical Research, University of Tubingen, Tubingen, Germany. Pedersen, Peter L. Departments of Biological Chemistry and Oncology, Member at Large, Sidney Kimmel Comprehensive Cancer Center, Johns Hopkins University, School of Medicine, Baltimore, MD, United States. Poore, Brad. The Sol Goldman Pancreatic Cancer Research Center, Department of Pathology, Johns Hopkins University School of Medicine, Baltimore, MD, United States. Poudyal, Deepak. College of Pharmacy, University of South Carolina, Columbia, SC, United States. Prakash, Satya. Department of Biomedical Engineering, McGill University, Montreal, Canada. Prince, Mark. Department of Otolaryngology-Head and Neck, Medical School, University of Michigan, Ann Arbor, MI, United States. Raffaghello, Lizzia. Laboratory of Oncology, Istituto Giannina Gaslini, Genoa, Italy. Rathmell, Jeffrey C. Duke Molecular Physiology Institute, Duke University Medical Center, Durham, NC, United States. Rathmell, W Kimryn. Lineberger Comprehensive Cancer Center, University of North Carolina, Chapel Hill, NC, United States. Ray, Swapan K. Department of Pathology, Microbiology, and Immunology, University of South Carolina, School of Medicine, Columbia, SC, United States. Reichrath, Jorg. Center for Clinical and Experimental Photodermatology, Clinic for Dermatology, Venerology and Allergology, The Saarland University Hospital, Homburg, Germany. Rezazadeh, Sarallah. Department of Biology, University of Rochester, Rochester, NY, United States. Ribatti, Domenico. Department of Basic Medical Sciences, Neurosciences and Sensory Organs, University of Bari Medical School, Bari, Italy & National Cancer Institute Giovanni Paolo II, Bari, Italy. Ricciardiello, Luigi. Department of Medical and Surgical Sciences, University of Bologna, Bologna, Italy. Robey, R Brooks. White River Junction Veterans Affairs Medical Center, White River Junction, VT, United States; Geisel School of Medicine at Dartmouth, Hanover, NH, United States. Rodier, Francis. Centre de Rechercher du Centre Hospitalier de l'Universite de Montreal and Institut du Cancer de Montreal, Montreal, Quebec, Canada; Universite de Montreal, Departement de Radiologie, Radio-Oncologie et Medicine Nucleaire, Montreal, Quebec, Canada. Rupasinghe, H P Vasantha. Department of Environmental Sciences, Faculty of Agriculture and Department of Pathology, Faculty of Medicine, Dalhousie University, Halifax, Nova Scotia, Canada. Russo, Gian Luigi. Institute of Food Sciences National Research Council, Avellino, Italy. Ryan, Elizabeth P. Department of Environmental and Radiological Health Sciences, Colorado State University, Fort Collins, CO, United States. Samadi, Abbas K. Sanus Biosciences, San Diego, CA, United States. Sanchez-Garcia, Isidro. Experimental Therapeutics and Translational Oncology Program, Instituto de Biologia Molecular y Celular del Cancer, CSIC-Universidad de Salamanca, Salamanca, Spain. Sanders, Andrew J. Cardiff University School of Medicine, Heath Park, Cardiff, United Kingdom. Santini, Daniele. Medical Oncology Department, University Campus Bio-Medico, Rome, Italy. Sarkar, Malancha. Department of Biology, University of Miami, Miami, FL, United States. Sasada, Tetsuro. Department of Immunology, Kurume University School of Medicine, Kurume, Fukuoka, Japan. Saxena, Neeraj K. Department of Medicine, University of Maryland School of Medicine, Baltimore, MD, United States. Shackelford, Rodney E. Department of Pathology, Louisiana State University, Health Shreveport, Shreveport, LA, United States. Shantha Kumara, H M C. Department of Surgery, St. Luke's Roosevelt Hospital, New York, NY, United States. Sharma, Dipali. Department of Oncology, Johns Hopkins University School of Medicine and the Sidney Kimmel Comprehensive Cancer Center at Johns Hopkins, Baltimore, MD, United States. Shin, Dong M. Winship Cancer Institute of Emory University, Atlanta, GA, United States. Sidransky, David. Department of Otolaryngology-Head and Neck Surgery, Johns Hopkins University School of Medicine, Baltimore, MD, United States. Siegelin, Markus David. Department of Pathology and Cell Biology, Columbia University Medical Center, New York, NY, United States. Signori, Emanuela. National Research Council, Institute of Translational Pharmacology, Rome, Italy. Singh, Neetu. Advanced Molecular Science Research Centre (Centre for Advanced Research), King George's Medical University, Lucknow, Uttar Pradesh, India. Sivanand, Sharanya. Department of Cancer Biology, Perelman School of Medicine, University of Pennsylvania, Philadelphia, PA, United States. Sliva, Daniel. DSTest Laboratories, Purdue Research Park, Indianapolis, IN, United States. Smythe, Carl. Department of Biomedical Science, Sheffield Cancer Research Centre, University of Sheffield, Sheffield, United Kingdom. Spagnuolo, Carmela. Institute of Food Sciences National Research Council, Avellino, Italy. Stafforini, Diana M. Huntsman Cancer Institute and Department of Internal Medicine, University of Utah, Salt Lake City, UT, United States. Stagg, John. Centre de Recherche du Centre Hospitalier de l'Universite de Montreal, Faculte de Pharmacie et Institut du Cancer de Montreal, Montreal, Quebec, Canada. Subbarayan, Pochi R. Department of Medicine, University of Miami Miller School of Medicine, Miami, FL, United States. Sundin, Tabetha. Department of Molecular Diagnostics, Sentara Healthcare, Norfolk, VA, United States. Talib, Wamidh H. Department of Clinical Pharmacy and Therapeutics, Applied Science University, Amman, Jordan. Thompson, Sarah K. Department of Surgery, Royal Adelaide Hospital, Adelaide, Australia. Tran, Phuoc T. Departments of Radiation Oncology & Molecular Radiation Sciences, Oncology and Urology, Johns Hopkins School of Medicine, Baltimore, MD, United States. Ungefroren, Hendrik. First Department of Medicine, University Hospital Schleswig-Holstein, Campus Lubeck, Lubeck, Germany. Vander Heiden, Matthew G. Koch Institute for Integrative Cancer Research, Massachusetts Institute of Technology, Cambridge, MA, United States. Venkateswaran, Vasundara. Department of Surgery, University of Toronto, Division of Urology, Sunnybrook Health Sciences Centre, Toronto, Ontario, Canada. Vinay, Dass S. Section of Clinical Immunology, Allergy, and Rheumatology, Department of Medicine, Tulane University Health Sciences Center, New Orleans, LA, United States. Vlachostergios, Panagiotis J. Department of Internal Medicine, New York University Lutheran Medical Center, Brooklyn, New York, NY, United States. Wang, Zongwei. Department of Urology, Massachusetts General Hospital, Harvard Medical School, Boston, MA, United States. Wellen, Kathryn E. Department of Cancer Biology, Perelman School of Medicine, University of Pennsylvania, Philadelphia, PA, United States. Whelan, Richard L. Department of Surgery, St. Luke's Roosevelt Hospital, New York, NY, United States. Yang, Eddy S. Department of Radiation Oncology, University of Alabama at Birmingham School of Medicine, Birmingham, AL, United States. Yang, Huanjie. The School of Life Science and Technology, Harbin Institute of Technology, Harbin, Heilongjiang, China. Yang, Xujuan. University of Illinois at Urbana Champaign, Champaign, IL, United States. Yaswen, Paul. Life Sciences Division, Lawrence Berkeley National Lab, Berkeley, CA, United States. Yedjou, Clement. Department of Biology, Jackson State University, Jackson, MS, United States. Yin, Xin. Medicine and Research Services, Veterans Affairs San Diego Healthcare System & University of California, San Diego, CA, United States. Zhu, Jiyue. Washington State University College of Pharmacy, Spokane, WA, United States. Zollo, Massimo. Centro di Ingegneria Genetica e Biotecnologia Avanzate, Naples, Italy; Department of Molecular Medicine and Medical Biotechnology, Federico II, Via Pansini 5, 80131 Naples, Italy.
Keywords: *Genetic Heterogeneity; *Molecular Targeted Therapy; *Neoplasms/th [Therapy]; *Precision Medicine; Antineoplastic Agents; Phytogenic; Antineoplastic Agents; Phytogenic/tu [Therapeutic Use]; Cancer hallmarks; Drug Resistance; Neoplasm; Drug Resistance; Neoplasm/ge [Genetics]; Genetic Heterogeneity; Humans; Integrative medicine; Molecular Targeted Therapy; Multi-targeted; Neoplasms; Neoplasms/ge [Genetics]; Neoplasms/pa [Pathology]; Neoplasms/pc [Prevention & Control]; Phytochemicals; Precision Medicine; Review; Signal Transduction; Targeted therapy; Tumor Microenvironment; Tumor Microenvironment/ge [Genetics]; anthocyanin; antineoplastic activity; antineoplastic agent; apoptosis; belinostat; berberine; breast cancer; cancer prevention; cancer therapy; cell immortalization; colorectal cancer; curcumin; deguelin; dept.bio; dietary intake; dinaciclib; drug cost; drug efficacy; drug resistance; drug safety; drug targeting; enterolactone; epigallocatechin gallate; gamma linolenic acid; genetic heterogeneity; genetics; genistein; genomic instability; gossypol; human; icosapentaenoic acid; imetelstat; inflammation; integrative medicine; interdisciplinary communication; kaempferol; luteolin; lycopene; melatonin; metastasis; metastasis inhibition; molecularly targeted therapy; naringenin; natural product; nonhuman; palbociclib; patent; pathology; perillyl alcohol; personalized medicine; phenotype; phytochemistry; recurrence risk; resveratrol; risk reduction; romidepsin; selinexor; signal transduction; silibinin; soybean; triptolide; tumor escape; tumor invasion; tumor microenvironment; tumor vascularization; unindexed drug; vorinostat; withaferin A; zerumbone

Cancer prevention and therapy through the modulation of the tumor microenvironment. - Casey, Stephanie C; Amedei, Amedeo; Aquilano, Katia; Azmi, Asfar S; Benencia, Fabian; Bhakta, Dipita; Bilsland, Alan E; Boosani, Chandra S; Chen, Sophie; Ciriolo, Maria Rosa; Crawford, Sarah; Fujii, Hiromasa; et al. (Seminars in Cancer Biology, 2015)
Cancer arises in the context of an in vivo tumor microenvironment. This microenvironment is both a cause and consequence of tumorigenesis. Tumor and host cells co-evolve dynamically through indirect and direct cellular interactions, eliciting multiscale effects on many biological programs, including cellular proliferation, growth, and metabolism, as well as angiogenesis and hypoxia and innate and adaptive immunity. Here we highlight specific biological processes that could be exploited as targets for the prevention and therapy of cancer. Specifically, we describe how inhibition of targets such as cholesterol synthesis and metabolites, reactive oxygen species and hypoxia, macrophage activation and conversion, indoleamine 2,3-dioxygenase regulation of dendritic cells, vascular endothelial growth factor regulation of angiogenesis, fibrosis inhibition, endoglin, and Janus kinase signaling emerge as examples of important potential nexuses in the regulation of tumorigenesis and the tumor microenvironment that can be targeted. We have also identified therapeutic agents as approaches, in particular natural products such as berberine, resveratrol, onionin A, epigallocatechin gallate, genistein, curcumin, naringenin, desoxyrhapontigenin, piperine, and zerumbone, that may warrant further investigation to target the tumor microenvironment for the treatment and/or prevention of cancer. Copyright © 2015 Elsevier Ltd. All rights reserved.
242 citations (Crossref) [2023-10-31] Place: England Casey, Stephanie C. Division of Oncology, Departments of Medicine and Pathology, Stanford University School of Medicine, Stanford, CA, United States. Amedei, Amedeo. Department of Experimental and Clinical Medicine, University of Florence, Florence, Italy. Aquilano, Katia. Department of Biology, University of Rome "Tor Vergata", Rome, Italy. Azmi, Asfar S. Department of Oncology, Wayne State University School of Medicine, Detroit, MI, United States. Benencia, Fabian. Department of Biomedical Sciences, Ohio University, Athens, OH, United States. Bhakta, Dipita. School of Chemical and Biotechnology, SASTRA University, Thanjavur 613401, Tamil Nadu, India. Bilsland, Alan E. Institute of Cancer Sciences, University of Glasgow, Glasgow, United Kingdom. Boosani, Chandra S. Department of Biomedical Sciences, School of Medicine, Creighton University, Omaha, NE, United States. Chen, Sophie. Ovarian and Prostate Cancer Research Laboratory, Guildford, Surrey, United Kingdom. Ciriolo, Maria Rosa. Department of Biology, University of Rome "Tor Vergata", Rome, Italy. Crawford, Sarah. Department of Biology, Southern Connecticut State University, New Haven, CT, United States. Fujii, Hiromasa. Department of Orthopedic Surgery, Nara Medical University, Kashihara, Japan. Georgakilas, Alexandros G. Physics Department, School of Applied Mathematics and Physical Sciences, National Technical University of Athens, Athens, Greece. Guha, Gunjan. School of Chemical and Biotechnology, SASTRA University, Thanjavur 613401, Tamil Nadu, India. Halicka, Dorota. New York Medical College, Valhalla, NY, United States. Helferich, William G. University of Illinois at Urbana-Champaign, Champaign-Urbana, IL, United States. Heneberg, Petr. Charles University in Prague, Third Faculty of Medicine, Prague, Czech Republic. Honoki, Kanya. Department of Orthopedic Surgery, Nara Medical University, Kashihara, Japan. Keith, W Nicol. Institute of Cancer Sciences, University of Glasgow, Glasgow, United Kingdom. Kerkar, Sid P. Center for Cancer Research, National Cancer Institute, National Institutes of Health, Bethesda, MD, United States. Mohammed, Sulma I. Department of Comparative Pathobiology, Purdue University Center for Cancer Research, West Lafayette, IN, United States. Niccolai, Elena. University of Florence, Florence, Italy. Nowsheen, Somaira. Medical Scientist Training Program, Mayo Graduate School, Mayo Medical School, Mayo Clinic, Rochester, MN, United States. Vasantha Rupasinghe, H P. Department of Environmental Sciences, Faculty of Agriculture, Dalhousie University, Nova Scotia, Canada. Samadi, Abbas. Sanus Biosciences, San Diego, United States. Singh, Neetu. Advanced Molecular Science Research Centre (Centre for Advanced Research), King George's Medical University, Lucknow, Uttar Pradesh, India. Talib, Wamidh H. Department of Clinical Pharmacy and Therapeutics, Applied Science University, Amman, Jordan. Venkateswaran, Vasundara. Division of Urology, Sunnybrook Health Sciences Centre, Toronto, Ontario, Canada. Whelan, Richard L. Mount Sinai Roosevelt Hospital, Icahn Mount Sinai School of Medicine, New York City, NY, United States. Yang, Xujuan. University of Illinois at Urbana-Champaign, Champaign-Urbana, IL, United States. Felsher, Dean W. Division of Oncology, Departments of Medicine and Pathology, Stanford University School of Medicine, Stanford, CA, United States. Electronic address: dfelsher@stanford.edu.
Keywords: *Carcinogenesis/de [Drug Effects]; *Neoplasms/dt [Drug Therapy]; *Neovascularization; Pathologic/dt [Drug Therapy]; *Tumor Microenvironment/ge [Genetics]; 5 chloro n2 [1 (5 fluoro 2 pyrimidinyl)ethyl] n4 (5 methyl 1h pyrazol 3 yl) 2; 4 pyrimidinediamine; Antineoplastic Agents; Antineoplastic Agents/tu [Therapeutic Use]; Cancer biology; Cancer prevention; Cancer therapy; Carcinogenesis; Carcinogenesis/ge [Genetics]; Cell Proliferation; Cell Proliferation/de [Drug Effects]; Humans; Janus kinase; Molecular Targeted Therapy; Neoplasms; Neoplasms/ge [Genetics]; Neoplasms/pc [Prevention & Control]; Neovascularization; Pathologic; Neovascularization; Pathologic/ge [Genetics]; Neovascularization; Pathologic/pc [Prevention & Control]; Review; Signal Transduction; Tumor Microenvironment; Tumor Microenvironment/de [Drug Effects]; Tumor microenvironment; antiinflammatory activity; antineoplastic agent; antioxidant activity; antiproliferative activity; apoptosis; bacterial infection; berberine; bevacizumab; cancer prevention; cancer therapy; candidiasis; carcinogenesis; cell proliferation; cholesterol synthesis; cisplatin; colorectal cancer; curcumin; cytokine production; dendritic cell; dept.bio; desoxyrhapontigenin; drug cytotoxicity; drug effects; drug potentiation; drug structure; drug targeting; endoglin; epigallocatechin gallate; fatty liver; fibrosis; genetics; genistein; genomic instability; glioblastoma; human; hydroxymethylglutaryl coenzyme A reductase inhibitor; hypercholesterolemia; hyperlipidemia; hypoxia; indoleamine 2; 3 dioxygenase; interleukin 6; kidney cancer; liver cancer; liver cell carcinoma; lung cancer; lung metastasis; macrophage activation; metastasis inhibition; molecularly targeted therapy; mycosis; naringenin; natural product; non insulin dependent diabetes mellitus; nonhuman; obesity; oncogene; onionin A; paclitaxel; pancreas tumor; parasitosis; piperine; reactive oxygen metabolite; resveratrol; signal transduction; sorafenib; stomach cancer

On the origins of autism: The Quantitative Threshold Exposure hypothesis. - Crawford, S (Medical hypotheses, 2015)
The Quantitative Threshold Exposure (QTE) hypothesis is a multifactorial threshold model that accounts for the cumulative effects of risk factor exposure in both the causation of autism spectrum disorder (ASD) and its dramatic increase over the past 30 years. The QTE hypothesis proposes that ASD is triggered by the cumulative effects of high-level exposure to endogenous and environmental factors that act as antigens to impair normal immune system (IS) and associated central nervous system (CNS) functions during critical developmental stages. The quantitative threshold parameters that comprise a cumulative risk for the development of ASD are identified by the assessment of documented epidemiological factors that, in sum, determine the likelihood that ASD will occur as a result of their effects on critically integrated IS and CNS pathways active during prenatal, neo-natal and early childhood brain maturation. The model proposes an explanation for the relationship between critical developmental stages of brain/immune system development in conjunction with the quantitative effects of genetic and environmental risk factors that may interface with these critical developmental windows. This model may be useful even when the individual contributions of specific risk factors cannot be quantified, as it proposes that the combined quantitative level of exposure to risk factors for ASD rather than exposure to any one risk factor per se defines threshold occurrence rates. Copyright © 2015 Elsevier Ltd. All rights reserved.
10 citations (Crossref) [2023-10-31] Place: United States Crawford, S. Department of Biology, Southern Connecticut State University, 501 Crescent Street, New Haven, CT 06515, United States. Electronic address: crawfords2@southernct.edu.
Keywords: *Autistic Disorder/ep [Epidemiology]; *Environmental Exposure/sn [Statistics & Numerical Data]; *Epidemiologic Methods; *Risk Assessment/mt [Methods]; *Threshold Limit Values; 5 HTT gene; 5 hydroxytryptophan; Article; Autistic Disorder; Causality; DNA polymorphism; Environmental Exposure; Epidemiologic Methods; Evidence-Based Medicine; Humans; Incidence; RLN gene; Risk Assessment; Threshold Limit Values; autism; autoimmune disease; brain dysfunction; brain maturation; cannabinoid 1 receptor; cannabinoid 2 receptor; cannabis use; central nervous system function; childhood disease; childhood feeding; copy number variation; dept.bio; developmental stage; disease association; disease severity; environmental exposure; environmental factor; epidemiological data; evidence based medicine; feeding; feeding behavior; genetic association; genetic predisposition; genetic risk; high risk population; human; hypothesis; immunoreactivity; incidence; infant feeding; intrauterine infection; n acetylgalactosaminidase; nervous system development; nonbiological model; nonhuman; pediatric infectious disease; perinatal period; prevalence; procedures; quantitative threshold exposure hypothesis; reelin; risk assessment; risk factor; statistics and numerical data; tetrahydrocannabinol; threshold limit value; threshold model; unclassified drug; unclassified enzyme; vitamin D deficiency

Physiological responses related to increased grain yield under drought in the first biotechnology‐derived drought‐tolerant maize - Nemali, Krishna S; Bonin, Christopher P; Dohleman, Frank G; Stephens, Mike; Reeves, William; Nelson, Donald E; Castiglioni, Paolo; Whitsel, Joy; Sammons, Bernard; Silady, Rebecca A; Anstrom, Donald; Sharp, Robert E; et al. (Plant Cell and Environment, 2015)
Maize (Zea mays ssp. mays L.) is highly susceptible to drought stress. This work focused on whole-plant physiological mechanisms by which a biotechnology-derived maize event expressing bacterial cold shock protein B (CspB), MON 87460, increased grain yield under drought. Plants of MON 87460 and a conventional control (hereafter 'control') were tested in the field under well-watered (WW) and water-limited (WL) treatments imposed during mid-vegetative to mid-reproductive stages during 2009-2011. Across years, average grain yield increased by 6% in MON 87460 compared with control under WL conditions. This was associated with higher soil water content at 0.5 m depth during the treatment phase, increased ear growth, decreased leaf area, leaf dry weight and sap flow rate during silking, increased kernel number and harvest index in MON 87460 than the control. No consistent differences were observed under WW conditions. This indicates that MON 87460 acclimated better under WL conditions than the control by lowering leaf growth which decreased water use during silking, thereby eliciting lower stress under WL conditions. These physiological responses in MON 87460 under WL conditions resulted in increased ear growth during silking, which subsequently increased the kernel number, harvest index and grain yield compared to the control. Copyright © 2014 The Authors. Plant, Cell & Environment published by John Wiley & Sons Ltd.
80 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/043-772-605-388-897 tex.type: [object Object]
Keywords: *Biotechnology/mt [Methods]; *Droughts; *Zea mays/ph [Physiology]; Bacteria (microorganisms); Bacterial Proteins; Bacterial Proteins/ge [Genetics]; Biotechnology; CspB; Droughts; Ear; Edible Grain; Harvest index; Leaf area; Plant Leaves; Plant Leaves/ph [Physiology]; Plants; Genetically Modified; Plants; Genetically Modified/ph [Physiology]; Sap flow; Soil; Soil water content; Soil/ch [Chemistry]; Water use; Yield; Zea mays; acclimation; adaptation; bacterial protein; biotechnology; chemistry; cold-shock protein CspB; Bacteria; crop yield; dept.bio; drought; drought stress; food grain; genetics; index method; leaf area; maize; physiological response; physiology; plant leaf; procedures; protein; sap flow; soil; soil water; tolerance; transgenic plant; water use efficiency